Teachers' Perceptions of Contemporary Literacy Learning Based on Folk Tales in Elementary Schools - Hidayah, Nurul; Bambang Edi Siswanto; Ganes Gunansyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Teachers' perceptions largely determine the extent to which traditional literature is integrated into contemporary primary school literacy education. However, research on how teachers interpret and apply local folktales in modern teaching contexts is limited. This study aims to describe teachers' perceptions of the moral values in the traditional story of Lembu Sura, their views on teaching strategies for traditional literature, and the associated challenges. The study employs both qualitative and quantitative methods. Seven teachers of Indonesian language classes for fifth and sixth grade students in the Papar district participated in the study. Data were collected through classroom observations, in-depth interviews, and documentation. The data were analyzed by summarizing, presenting, and drawing conclusions. The results showed that all of the teachers rated teaching the Lembu Sura folktale as having a positive impact on students' character formation and literacy development. However, several main issues were identified. First, 57.1% of the teachers reported a lack of teaching materials. Second, 85.7% of teachers reported that students had difficulty understanding the meaning of curses and the symbolism of the transformation into Mount Kelud. Third, 57.1% of teachers noted the limited availability of innovative media and low interest in reading local literature. These findings underscore the necessity of developing digital learning media, more contextualized teaching materials, and training for teachers to help them integrate traditional literature more effectively into contemporary literacy education.